The Incidence of Chronic Peptic Ulcer Found at Necropsy: A Study of 20, 000 Examinations Performed in Leeds in 1930-49 and in England and Scotland in 1956. Issue 1 (March 1960) - Watkinson, Geoffrey
Abstract : In this study the frequency of gastric, duodenal, and stomal ulcer has been determined in a survey at necropsy. This survey is likely to be much more accurate than those previously reported, as it has been a "forward planned" one and conducted by a group of men interested in this subject. In retrospective studies it is always impossible to know how carefully a particular point has been checked. It has been concluded from this study that the best estimate of the incidence of ulcer in the population as a whole can be made from the frequency of ulcers found in patients dying from causes other than peptic ulcer. The incidence of such active ulcers accords closely with clinical experience in life.